Hukum Bedah Mayat dalam Perspektif Maqashid Asy-Syari’ah - Indah Widya Jaya Putri Nasution; Muhammad Irfansyah Siregar; Ummi Nadrah Nasution; Predi Ari Repi; Ade Ilfah; Ali Imran Sinaga (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Nowhere in the Qur’an or even in the hadith does it speak about the law of post-mortems. But the fact is that currently, various criminal acts occur that lead to death, and the cause of death cannot even be known, so an autopsy is carried out. And even the practice of post-mortem surgery is carried out by medical students under the auspices of a post-mortem surgeon to determine the structure of the human body's organs. Therefore, the aim of this research is to find out and explore how Islamic law views in responding to the increasingly advanced development of knowledge regarding post-mortems. This research uses library research, where the data sources used come from various books, journals and articles which are then processed and analyzed using a descriptive analysis approach. The results of this research are, basically the law prohibits post-mortems from being carried out, but to consider the public benefit, post-mortems are permitted, such as; Hifz Al-din, Hifz al-Nafs, Hifz Al-Nasl, Hifz al-Mal, and Hifz al-‘Aql